Fungal Infections among Psoriatic Patients: Etiologic Agents, Comorbidities, and Vulnerable Population. (16th September 2021) - Chadeganipour, Mostafa; Shadzi, Shahla; Mohammadi, Rasoul
Abstract : Background . Psoriasis is a chronic inflammatory disorder of the skin and joint, affecting nearly 2-3% of the general population. It is assumed that imbalance between the types of natural microflora can accelerate the onset of the disease. Some fungi can play the role of superantigens and prolong chronic inflammation in the skin of psoriatic patients. The aim of the present investigation was to identify fungal species isolated from patients with psoriasis. Methods . From March 2016 to May 2019, 289 patients with prior diagnosis of psoriasis were included in this survey. Direct microscopy with potassium hydroxide (KOH 10%), culture, urea hydrolysis, hair perforation test, and growth on rice grains were used to identify clinical isolates, phenotypically. For molecular identification of Candida species and Malassezia species, PCR-RFLP and PCR-sequencing were used, respectively. Results . Forty-six out of 289 psoriatic patients had fungal infections (15.9%). Dermatophytes (54.3%), Candida spp. (19.5%), Malassezia spp. (15.2%), Aspergillus spp. (6.5%), and Fusarium spp. (4.3%) were the causative agents of fungal infections. Among Malassezia and Candida species, M. restricta (10.8%) and C. glabrata (8.7%) were the most prevalent species, respectively. Conclusion . Our findings suggested that fungal pathogens, particularly dermatophytes, may play an important role in the pathogenicity of psoriasis. Also, due to the high rate of yeast colonization in the clinical samples of psoriatic patients, concomitant use of anti-inflammatory drugs and antifungals may represent an effective therapeutic approach for better management of chronic lesions among these patients. Mycological tests should be applied to indicate the incidence of fungal diseases in psoriatic patients.